Geography and the Military: Notes for a Debate. Issue 3 (3rd May 2016) - Bryan, Joe
Abstract : In the United States, Geography and the military have never been far apart. Their intertwined history has been essential to the discipline's institutional reproduction and the workings of U.S. imperialism. Recent instances of militarism in Geography return this history to the fore, posing a number of challenges. They demonstrate the futility of geographical research for its own sake, naïvely assuming that knowledge of the world produced by geographers is inherently neutral. That same attitude leaves Geography powerless to confront its utility to the military, treating the discipline's militarization as an inevitable coincidence. The current appearance of militarism in U.S. Geography proves both positions untenable. Confronting the extent of this relationship, both past and present, draws attention to how militarism shapes Geography's objects of inquiry and methods of research. That effort must be matched by documentation of the variety of ways in which geographical knowledge is appropriated for military ends. The task is enormous and can only be done collectively lest geographers want to blindly surrender the legitimacy of the discipline to its military application.